Elevated serum TLR4 level as a potential marker for postsurgical chronic pain in pediatric patients with different approaches to analgesia - Semkovych, Yaroslav; Dmytriiev, Dmytro (Frontiers in Medicine, 2022)
The level of Toll-like receptor 4 (TLR4) is known to increase in inflammation and after nerve injury and contributes to the development of neuropathic pain. The interaction of TLRs in response to the effect of opioids results in hyperalgesia. The aim of the study was to determine and evaluate the indicators of TLR4 for different methods of pain relief in children and their effect on pain chronification. Materials and Methods. There were examined 60 children with inguinal hernia during 2020-2022. Children were divided into 3 groups: Group I included 20 children who underwent surgery under general anesthesia using the block of the anterior abdominal wall - transversalis fascia plane block (TFPB), combined with the quadratus lumborum block (QLB-4) via a single intramuscular injection; Group II included 20 children who underwent surgery under general anesthesia using the TFPB; Group III comprised 20 children who underwent surgery under general anesthesia using opioid analgesics. The levels of TLR4 were evaluated at a discharge from the hospital, 3 and 6 months after surgery. Results. There was no difference in age and body weight among all groups. In Group II, boys prevailed. In Group III, the length of hospital stay was the longest (3.28±0.24 days) as compared to children of Group II and Group I (3.0±0.30 and 2.1±0.16 days (р<0.05), respectively). While staying in the surgical department, children of Group III demonstrated significantly higher FLACC and VAS scores. The prevalence of chronic pain was the highest among children of Group III (35%) as compared to those in Group II and Group I (20 and 15%, respectively). The highest increase in the level of TLR4 was found in the group of opioid analgesia on the third and sixth months after surgery (68.86+10.31 pg/ml and 143.15+18.77 pg/ml (р<0.05), respectively) as compared to patients who received regional anesthesia. Conclusions. There were confirmed the following advantages of the transversalis fascia plane block combined with the quadratus lumborum block (QLB+TFPB) via a single intramuscular injection: ease of use; adequate perioperative pain control as evidenced by the FLACC and VAS pain assessment scales.